Magnetism in carbon-based fiber materials - Ranade, Varun; Gautam, Sanjeev; Chae, Keun Hwa (Elsevier BV, 2023)
Metal-free ferromagnetic materials have gained significant attention as an appealing alternative to traditional inorganic magnets due to their biocompatibility, biodegradability, low production cost, flexibility, solubility in organic solvents, and electrical insulation properties. These features make them highly desirable for biomedical and spintronic applications. The origin of magnetism in these materials is linked to the presence of unpaired electrons, defects, or functional groups that induce local magnetic moments. However, achieving ferromagnetic interaction among persistent carbon radicals within a molecule has been a challenging endeavor. Various strategies have been explored to induce ferromagnetism in carbon-based materials, including defect induction, steric hindrance, and doping with trivalent or pentavalent species like Boron (B) and Nitrogen (N). These approaches have successfully led to the development of organic magnets in different dimensions, ranging from 0D to 3D.Recent advancements in synthesizing organic magnets exhibiting ferromagnetism above room temperature have reignited interest among physicists and chemists in the realm of organic spintronic materials. Furthermore, the integration of magnetic nanoparticles into carbon nanotubes has been a prominent research focus. Understanding the underlying mechanisms of magnetism in carbon-based polymers, such as graphene, carbon nanotubes, and fullerenes, has been the subject of extensive studies over the past few decades. This article presents a critical review of recent research on carbon-based magnetic polymers, including their limitations and applications. The emergence of magnetism in carbon-based 2D materials holds immense potential for spintronics and high-density data storage applications, contributing to the advancement of quantum computing and empowering artificial intelligence.